Interviewing Dr Felipe Fregni: A Pathway to a Research Career - Juliana Bonilla-Velez; Whitney Stefanny Cordoba-Grueso (University Library System, University of Pittsburgh, 2015)
A talented Brazilian physician investigator, Felipe Fregni, is an Associate Professor of Physical Medicine & Rehabilitation and Neurology at Harvard Medical School, where he directs the Neuromodulation Laboratory at the Department of Physical Medicine & Rehabilitation at Spaulding Rehabilitation Hospital & Massachusetts General Hospital. He completed his medical studies, Neurology residency, and a Doctor of Philosophy (PhD) at the University of Sao Paulo and continued on to pursue postgraduate studies as well as a Master of Public Health (MPH) at Harvard Medical School. His philanthropic nature led him to design the Collaborative Learning in Clinical Research Program and the Principles and Practice of Clinical Research course with the Department of Continuing Education at Harvard Medical School to educate on basic and advanced training in clinical trials for physicians around the world. As part of this course, he has reached to physicians and students of graduate and postgraduate studies in the medical field in 30 countries to offer a 9-month collaborative distance-learning course on clinical research. For this interview, he was invited to share his experiences and insight as a physician-scientist from Brazil with medical students worldwide.